GARCÍA MARQUÉS, A. (2019). Pensando el sujeto: Aristóteles y Quine. Madrid: Dykinson. - Francisco Andrés Haro Almansa (Daimon)
Reseña de: GARCÍA MARQUÉS, A. (2019). Pensando el sujeto: Aristóteles y Quine. Madrid: Dykinson.